Development of nanocomposite Fe3O4@Au-modified electrode and application to chloramphenicol determination with electrochemical method - Hồ, Văn Minh Hải; Đặng , Xuân Tín; Lê, Thị Hòa; Nguyễn, Đức Vũ Quyên; Bui, Thị Hoàng Diễm; Nguyễn, Thị Thảo Uyên; Võ, Thế Kỳ; Nguyễn, Văn Cường; Nguyễn, Ngọc Nghĩa (Hue University Journal of Science: Natural Science, 2023)
In this work, the Fe3O4 porous microstructures were synthesized with the thermal hydrolysis method. It was found that Fe3O4 exhibits a large specific surface area, consisting of hierarchical self-assembly of sheet-like nanoparticle subunits. Furthermore, Au nanoparticles with an average size of 10 nm were decorated uniformly on the surface of Fe3O4 through a simple chemical reduction method. The obtained Fe3O4@Au porous nanocomposite was modified onto the glassy carbon electrode, and the modified electrode was applied to determine chloramphenicol. The proposed electrode exhibits a linear range of 2–10 μM and a low limit of detection of 0.17 μM.